2016
DOI: 10.1111/exd.13137
|View full text |Cite
|
Sign up to set email alerts
|

Desired response to phototherapy vs photoaggravation in psoriasis: what makes the difference?

Abstract: Psoriasis commonly responds beneficially to UV radiation from natural sunlight or artificial sources. Therapeutic mechanisms include the proapoptotic and immunomodulating effects of UV, affecting many cells and involving a variety of pro-and anti-inflammatory cytokines, downregulating the Th17/IL-23 response with simultaneous induction of regulatory immune cells. However, exposure to UV radiation in a subset of psoriasis patients leads to exacerbation of the disease. We herein shed light on the predisposing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 133 publications
1
32
0
1
Order By: Relevance
“…Notably, our results showed a very low prevalence of PLE in psoriasis patients undergoing phototherapy (0.7%, [3/421]), even though PLE in psoriasis might not be so rare in the general population . PLE seems to be highly linked to photosensitive variants of psoriatic disease.…”
Section: Discussionmentioning
confidence: 66%
“…Notably, our results showed a very low prevalence of PLE in psoriasis patients undergoing phototherapy (0.7%, [3/421]), even though PLE in psoriasis might not be so rare in the general population . PLE seems to be highly linked to photosensitive variants of psoriatic disease.…”
Section: Discussionmentioning
confidence: 66%
“…A better understanding of the pathogenesis of psoriasis and the UV therapeutic mechanism(s) should contribute to the desired optimization of a sustainable and effective UV treatment of psoriasis as a chronic disease. The Viewpoint of Wolf et al . on the desired versus adverse responses to phototherapy provides several leads for the optimization.…”
Section: Resultsmentioning
confidence: 99%
“…Recent works have also suggested that innate antimicrobial peptides (AMP) may be involved in pathogenesis of PLE . Normally, UVR‐induced AMP contributes to immunosuppression inducing Tregs, otherwise in early stages of PLE a dysregulated AMP expression following UVR could play some part in the failure of photoimmunosuppression .…”
Section: Discussionmentioning
confidence: 99%